Relapsing neurological disorder associated with rubella virus infection in two sisters. Issue 11 (November 1977) - Callaghan, N; Feely, M; Walsh, B
Abstract : A disseminated relapsing neurological disorder presented simultaneously in two sisters. Encephalitic features were present in one case. The illness was associated with a significant increase in rubella specific IgM in both sisters. Despite the absence of a rubella rash, this increase would be compatible with a recent infection by the rubella virus as a basis for the illness, and the persistent elevation, with active antigenic stimulation. It is suggested that both patients might represent the clinical manifestations of perivenous demyelination caused by the rubella virus, which, in view of the relapsing nature of the illness, has progressed to plaque formation.